The Effect of Therapeutic Group Therapy and Family Psychoeducation on Adolescent Self-Identity - Pulungan, Zulhaini Sartika A.; Keliat, Budi Anna; Hamid, Achir Yani S. (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Adolescence is a period in the span of human life that is most critical. The developmental task of adolescents in the age range of 11-20 years is to achieve self-identity. Adolescents can be given stimulation with therapeutic group therapy (TGT) and family psychoeducation (FPE) to improve their self-identity. The aim of the study was to determine the effect of giving therapeutic group therapy (TGT) and family psychoeducation (FPE) on increasing adolescent self-identity. Quasi-experimental research with pre-posttest with control group design. The sample is 32 people with purposive sampling technique which is divided into two groups. The intervention group 1 was given TGT and FPE while the intervention group 2 was only given TGT. Data analysis used paired t-test and independent sample t-test. The results showed that there were significant differences between the 1st and 2nd intervention groups in terms of cognitive and language (p value = 0.004), emotional and psychosocial (p value = 0.041), talent and creativity (p value = 0.011). There was a significant difference in self-identity between the 1st and 2nd intervention groups (p value = 0.004). Therapeutic group therapy (TGT) and family psychoeducation (FPE) improve the ability of adolescent self-identity. Adolescent therapeutic group therapy can be carried out in the setting of health services in the community as a form of mental health nursing service and can also be applied in community service activities.